Identification of Characteristic Fatty Acids to Quantify Triacylglycerols in Microalgae - Shen, Pei-Li; Wang, Hai-Tao; Pan, Yan-Fei; Meng, Ying-Ying; Wu, Pei-Chun; Xue, Song (Frontiers in Plant Science, 2016)
The fatty acid profiles of lipids from microalgae are unique. Polyunsaturated fatty acids are generally enriched in polar lipids, whereas saturated and monounsaturated fatty acids constitute the majority of fatty acids in triacylglycerols (TAG). Each species has characteristic fatty acids, and their content is positively or negatively correlated with TAGs. The marine oleaginous diatom Phaeodactylum tricornutum was used as the paradigm to determine the quantitative relationship between TAG and characteristic fatty acid content. Fatty acid profiles and TAG content of Phaeodactylum tricornutum were determined in a time course. C16:0/C16:1 and eicosapentaenoic acid (EPA, C20:5n3) were identified as characteristic fatty acids in TAGs and polar lipids, respectively. The percentage of those characteristic fatty acids in total fatty acids had a significant linear relationship with TAG content and thus the correlation coefficient presenting r2 were 0.96, 0.94 and 0.97 respectively. The fatty acid-based method for TAG quantification could also be applied to other microalgae such as Nannochloropsis oceanica in which the r2 of C16:0, EPA were 0.94, 0.97 respectively and Chlorella pyrenoidosa, whose r2 value correspondingly between C18:1, C18:3 and TAG content were 0.91, 0.99 as well. This characteristic fatty acid-based method provided a distinct way to quantify TAGs in microalgae, by which TAGs could be measured precisely by immediate transesterification from wet biomass rather than using conventional methods. This procedure simplified the operation and required smaller samples than conventional methods.